The investment in the education in Madre de Dios - Molina Bocangel, Rolando Alberto (2019)
The present research seeks to determine the impact of the current levels of investment destined to education in the formation of human capital that sustain growth and economic development in Madre de Dios. The type of research is descriptive, explanatory and correlational.In conclusion, it was determined that the best levels of investment destined to education are important for the formation of human capital that supports growth and economic development.